Surface morphologies and microstructure of high-strength steel AISI 4820 with different heat treatment during grinding process. (30th June 2023) - Zhong, Bingfu; Dang, Jiaqiang; An, Qinglong; Chen, Ming
Abstract: High-strength steel AISI 4820 has been widely used in the manufacturing process for functional components (gear parts) at varying service environments. Surface morphologies and microstructure caused by the grinding process have important implications for the service life of components, which can be determined by the machining parameters and heat treatment conditions. In this paper, to further understanding of underlying deformation mechanism of AISI 4820 induced by grinding parameters, the surface morphologies and microstructure of AISI 4820 steel with three different heat treatment conditions, i.e., the carburized and quenched heat treatment (CQHT), the normalized heat treatment (NHT), the quenched heat treatment (QHT), during the grinding process was investigated. Surface morphologies analysis by SEM. The microstructure, plastic deformation, and grain refinement mechanism was revealed by EBSD. The results showed that better machined surface quality is performed in the CQHT condition. In NHT condition, the subsurface layer grains were significantly deformed and refinement was exhibited after the grinding process in NHT condition. Additionally, the internal grains were refined after carburizing in QHT condition.